Ionisation of noble gas atoms and H2O by antiproton impact - Abdurakhmanov, Ilkhom; Kadyrov, Alisher; Fursa, Dmitry; Avazbaev, S.; Bailey, J.; Bray, Igor (2015)
© Published under licence by IOP Publishing Ltd. A time-dependent convergent close-coupling approach to antiproton collisions with noble gas atoms and H2O has been developed using a fully multielectron treatment of the targets. Integrated cross sections for single ionisation have been calculated in a wide range of impact energies from 5 keV up to 2 MeV. Obtained results are in good agreement with experiment.